Association Between the Use of Proton Pump Inhibitors and the Risk of ESRD in Renal Diseases: A Population-Based, Case-Control Study. Issue 15 (April 2016) - Peng, Yen-Chun; Lin, Cheng-Li; Yeh, Hong-Zen; Chang, Chi-Sen; Wu, Yu-Lin; Kao, Chia-Hung
Abstract : Abstract: Proton pump inhibitors (PPIs) use may be associated with nephritis and acute renal injury. The risk of PPIs and deterioration of renal function, in patients with renal diseases, needs to be investigated. A case-control study was conducted in a nation-wide data setting from the Taiwan National Health Insurance Research Database (NHIRD). This case-control study used data extracted from NHIRD between the years 2006 and 2011. We used propensity scores to match 3808 patients suffering from renal diseases (ICD-9-CM codes 580–589), with patients (aged ≥20 years) who had had a recent diagnosis of end-stage renal diseases (ESRDs) and had undertaken renal replacement therapy during the period of 2006 to 2011. The 3808 control subjects were selected from people who had a history of renal diseases, but no ESRD. The risk of ESRD in patients with renal diseases and PPIs use was estimated by using odds ratios (ORs) and 95% confidence intervals (CI). The use of a PPIs was associated with a significantly higher risk of ESRD (adjusted OR = 1.88, 95% CI = 1.71–2.06) in renal disease patients. Of all the types of PPI combined, the adjusted OR was 1.92 (95% CI = 1.74–2.13) for those on <100 cumulative DDD and was 1.74-fold (95% CI = 1.52–2.00) for those on ≥100 cumulative DDD. PPIs use is associated with the risk of ESRD in patients with renal diseases. It is necessary that appropriate prescription of PPIs coordinated with the close monitoring renal function of patients diagnosed with renal disease.